(untitled) (Sociologisk Forskning, 2000)
In this paper it is hypothesised that individuals’ ability to cope with the Russian transition is socially structured and will give rise to health differences and differences in ‘risk behaviours’. Since self-rated health and mortality represent different dimensions of public health and since risk behaviours have been closely related to mortality, we wanted to examine whether (poor) self-rated health on the one hand and risk behaviours on the other can be attributed to different causes. The Taganrog household survey was conducted in the form of face-to face interviews and included 1009 individuals and their families.The survey was carried out January to December 1998. To estimate health differences and differences in risk behaviours between groups, logistic regressions were performed. In Taganrog between 1993/94 and 1998, changes in public health, (here self-rated health), seem to have been much more dramatic than changes in smoking and different in direction than changes in heavy alcohol consumption. Moreover, self-rated ‘poor’ health was more common among those whose economic situation was worse 1998 than ten years before. However, having a poorer economy during the period 1988-1998, does not seem to have affected drinking or smoking habits significantly. In general, self-rated health seems to be more closely related to three indicators of economic circumstances. Risk behaviours are certainly im portant for the poor state of public healthin Russia, but may be not closely connected to the economic aspects of the transition.